Influence of MgO and Hybrid Fiber on the Bonding Strength between Reactive Powder Concrete and Old Concrete - Mo Jinchuan; Ou Zhongwen; Wang Yahui (Advances in Materials Science and Engineering)
The reactive powder concrete (RPC) was used as concrete repair material in this paper. The influence of steel fiber, steel fiber + MgO, and steel fiber + MgO + polypropylene fiber (PPF) on the mechanical properties of RPC repair materials and the splitting tensile strength between RPC and old concrete was studied. Influences of steel fiber, MgO, and PPF on the splitting tensile strength were further examined by using scanning electronic microscopy (SEM) and drying shrinkage test. Results indicated that the compressive and flexural strength was improved with the increasing of steel fiber volume fraction. However, the bonding strength showed a trend from rise to decline with the increasing of steel fiber volume fraction. Although MgO caused mechanical performance degradation of RPC, it improved bonding strength between RPC and existing concrete. The influence of PPF on the mechanical properties of RPC was not obvious, whereas it further improved bonding strength by significantly reducing the early age shrinkage of RPC. Finally, the relationship of drying shrinkage and splitting tensile strength was studied, and the equation between the splitting tensile strength relative index and logarithm of drying shrinkage was obtained by function fitting.